Correlation Analisys Between Seed Weight And Seed Germination Of The Rao Plant (Dracontomelon dao, Hask) - Johan Markus Matinahoru (Agrologia, 2022)
Rao plants are very suitable for reforestation and land rehabilitation activities because they have big trees, dense canopy and deep roots, and also strong roots. However, in its development, it still has problems, namely the low percentage of seed germination because the seeds of this species are semi-recalcitrant seeds, and have seed coat dormancy. Seed weight is thought to have a relationship with the success of germination and growth of rao plants. Therefore, the purpose of this study was to determine the relationship between seed weight and germination time and also the speed growth of germination. The method used in this study is a correlation test with a simple regression analysis approach. The variables used were the seed weight variable as the X factor, and the germination time and rates as the Y factor. The results of the study of 100 seeds of rao plants that were sampled in this study had variations in seed weight ranging from 2.1 to 5 grams. The germination time for each seed ranged from 9 – 62 days with an average growth rate of 1.8 – 3.9 cm per week. The variation in the growth time of each seed is due to the fact that the seeds of the rao plant have seed coat dormancy, but in this study there was no treatment to overcome this dormancy, so the germination process depends on the natural process of each seed. Based on the results of the study, it can be concluded that: (1) the average germination time of rao (Dracontomelon dao, Hask) seeds was 30 days, (2) seed weight was strongly correlated with seed germination time and seed germination rate, (3) seed weight increased, the germination time is longer, but the rate of growth of seed germination is faster